Effect Of Habit Pronunciation Greetings On Morals - stitlakbok, stitlakbok (Andi Anugrah, 2021)
The purpose of this study was to prove the influence of pronunciation habits in regards to morals religious adherents Islam Metoda study is aquantitative study using infrenesia statistical analysis, using the model of correlation analysis (Pearson product moment), the number of respondents is40 people, which is performed on MI Minaul 'Ulum Banjar, in the month of September 2014 (. the results showed that the pronunciation habits greetingpositive and significant influence on morals